DOMESTIC VIOLENCE AGAINST WOMEN: A HISTORIC AND SOCIO-CULTURAL REALITY IN BANGLADESH - Mohiuddin Ahsanul Kabir Chowdhury; Salma Morium (European Scientific Journal, ESJ, 2015)
Domestic violence against women is prevalent throughout the world in different forms even in this twenty first century. Though the view towards domestic violence varies across the countries the World Bank has already spotted it as a global epidemic. Domestic violence, whether in urban or rural areas, puts women community at vulnerable position as it causes both physical and psychological grievances. Several forms of domestic violence including physical, psychological, sexual and economical violence have been illustrated by different organizations worldwide. In Bangladesh, the patriarchal capitalism puts women in such a position that they always remain subservient under mail domination and in many cases this is reflected through violence against them. This was criminalized in Bangladesh in 2010. But the laws are not enough alone to protect the women from sufferings. Strategies should be taken to raise the awareness among the general population along with effective implementation of the law. This paper depicts an overview on domestic violence against women from socio-cultural and legal perspective emphasizing especially over the situation in Bangladesh.